The Influence of the School Literacy Movement through the Utilization of Reading Angles on Reading Interest of Elementary School Students: Pengaruh Gerakan Literasi Sekolah Melalui Pemanfaatan Sudut Baca Terhadap Minat Baca Siswa Sekolah Dasar - Ana, Ria Fajrin Rizqy (Pedagogia : Jurnal Pendidikan, 2020)
The purpose of this study is to determine the effect of the School Literacy Movement on students' interest in reading at Kendalrejo 01 Public Elementary School. This study used a quantitative approach with an ex post facto method. The instruments used were questionnaires and learning outcomes. The results showed the value of t_ (count) of 5.498, while t_table is known to be 1.987, then 5.498> 1.987. So it can be concluded that there is a significant effect of the School Literacy Movement on the reading interest of students at SDN Kendalrejo 01 with a coefficient of determination of 25.4%.